2011
DOI: 10.4061/2011/846756
|View full text |Cite
|
Sign up to set email alerts
|

Conjugate Meningococcal Vaccines Development: GSK Biologicals Experience

Abstract: Meningococcal diseases are serious threats to global health, and new vaccines specifically tailored to meet the age-related needs of various geographical areas are required. This paper focuses on the meningococcal conjugate vaccines developed by GSK Biologicals. Two combined conjugate vaccines were developed to help protect infants and young children in countries where the incidence of meningococcal serogroup C or serogroup C and Y disease is important: Hib-MenC-TT vaccine, which offers protection against Haem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 85 publications
(166 reference statements)
1
21
0
3
Order By: Relevance
“…21 Immunogenicity and effectiveness Phase II and III studies showed that a single dose of MenACWY-TT was highly immunogenic in toddlers, children, adolescents, and adults one month following vaccination. 108 MenACWY-TT showed non-inferiority to MPV-4 in terms of immunogenicity to the 4 serogroups in adults aged 18-55 y, with significantly higher antibody titers against serogroups A, W-135, and Y one month post-vaccination. 30,109 In subjects 10-25 y of age, SBA titers were also higher for these 3 serogroups in recipients of MenACWY-TT compared with MenACWY-DT.…”
Section: Concomitant Vaccinationsmentioning
confidence: 92%
See 1 more Smart Citation
“…21 Immunogenicity and effectiveness Phase II and III studies showed that a single dose of MenACWY-TT was highly immunogenic in toddlers, children, adolescents, and adults one month following vaccination. 108 MenACWY-TT showed non-inferiority to MPV-4 in terms of immunogenicity to the 4 serogroups in adults aged 18-55 y, with significantly higher antibody titers against serogroups A, W-135, and Y one month post-vaccination. 30,109 In subjects 10-25 y of age, SBA titers were also higher for these 3 serogroups in recipients of MenACWY-TT compared with MenACWY-DT.…”
Section: Concomitant Vaccinationsmentioning
confidence: 92%
“…60,108 In adults, the most frequently reported local adverse events were pain (25.3%), redness (10.3%) and swelling (8.5%), and general adverse events were headache (15.8%) followed by fatigue (13%), gastrointestinal symptoms (4.7%), and fever (4%). 110 Studies in 10-to 25-y-old subjects receiving either MenACWY-TT or MenACWY-DT showed that pain and headache were the most commonly reported solicited local and general adverse events, respectively, occurring at a similar rate in both groups.…”
Section: Concomitant Vaccinationsmentioning
confidence: 99%
“…Another drawback of these vaccines is that they induce hypo responsiveness on repeated dosing and have little or no effect on nasopharyngeal carriage and consequently on herd immunity. 7,13,16,33,34 Several conjugate vaccines have been licensed in the past decade to overcome the limitations posed by the PS vaccines. 16 In these vaccines, the capsular PS is coupled to a carrier protein with a T-cell epitope that would induce T-cell dependent response.…”
Section: Prevention Of Diseasementioning
confidence: 99%
“…7,13,16,33,34 Several conjugate vaccines have been licensed in the past decade to overcome the limitations posed by the PS vaccines. 16 In these vaccines, the capsular PS is coupled to a carrier protein with a T-cell epitope that would induce T-cell dependent response. Thus, the result would be an improved immune response in infants, induction of immune memory and higher bactericidal antibody titers and consequently longer antibody persistence.…”
Section: Prevention Of Diseasementioning
confidence: 99%
See 1 more Smart Citation